Twelve-month mortality from the "How Effective are Antithrombotic Therapies in Primary Percutaneous Coronary Intervention (HEAT-PPCI) Trial". (1st July 2020) - Blake, Sarah R.; Shahzad, Adeel; Kemp, Ian; Mars, Christine; Wilson, Keith; Stables, Rod H.
Abstract: Background: There is ongoing uncertainty regarding the safety and efficacy of unfractionated heparin and bivalirudin when used for systemic anticoagulation in patients undergoing primary percutaneous coronary intervention (PPCI). This paper reports 12-month mortality from the HEAT-PPCI randomised trial. Methods: In this open-label, randomised controlled trial (RCT) we enrolled consecutive adults with suspected ST-elevation myocardial infarction (STEMI). Patients were randomised to heparin (bolus 70 U/kg) or bivalirudin (bolus 0.75 mg/kg followed by an infusion 1.75 mg/kg/h for the duration of the procedure). We report the pre-specified secondary outcome of all-cause mortality at 12 months. Mortality was classified as cardiovascular or not, blinded to treatment allocation. Deaths in the first 28 days were classified by formal event adjudication and later events classified from death certificates. Results: Mortality status at 12 months was obtained for 1805/1812 = 99.6% of participants. Overall mortality was 160/1812 = 8.9%. There were more deaths in those randomised to bivalirudin (95/902 = 10.5% vs 65/903 = 7.2%; HR 1.48; 95% CI 1.08 to 2.03; p = 0.015). Most deaths were classified as cardiovascular (71/902 = 7.9% in the bivalirudin group and 53/904 = 5.9% in the heparin group). The difference between the rates of cardiovascular deaths in each treatment group did not reach statistical significance: HR 1.35; 95% CI 0.95 to 1.93; p = 0.095. Conclusions: At 12 months, treatment with bivalirudin, rather than heparin, was associated with a higher rate of all-cause mortality. Cardiovascular mortality was higher with bivalirudin although this difference was not statistically significant. Highlights: Use of bivalirudin in PPCI was associated with a significantly higher risk of all-cause mortality at 12 months. Cardiovascular causes of death at 12 months were not significantly different between the treatment groups. There was a statistically significant difference in non-cardiovascular deaths that may have occurred by chance.